IMPROVING LISTENING SKILLS FOR JUNIOR HIGH SCHOOL USING POWTOON VIDEO (RETAIN, 2023)
Listening is one of the basic components that may help us in learning or in our daily life. As we all know, listening skill is a crucial ability for students since it allows us to learn how to pronounce words and prepares ourselves to interact with others. The purpose of the study is to investigate whether using PowToon as an alternative media enhances students’ listening skills, and to find out students’ responses towards learning listening through PowToon as an alternative media The method used in this study is quantitative, with 30 students in grade 8th in one of the public junior high schools in Surabaya as the participants. From the answers to the questionnaire, some students thought that using PowToon videos could not help them to improve their listening skills, but students thought that learning using PowToon videos was interesting and fun. The result of this study also showed that PowToon video did not bring significance to the listening skills of junior high school students (p-value=0.34, > 0.05).